Inhibition of in vitro gamete adhesion and in vivo fertility in mice by immunization with a synthetic peptide - Fuentes, P (Clinical immunology (Orlando, Fla.), 2006)
PROBLEM: To evaluate the contraceptive ability of a synthetic peptide in in vitro and in vivo fertility in the mouse